A study on the knowledge, beliefs and practices of patients diagnosed with tuberculosis in katutura, khomas region, Windhoek - Kamenye, Esther; Sumpi, Ndemupavali; van Dyk, Agnes; Ashipala, Daniel (International Journal of Advanced Nursing Studies, 2016)
Tuberculosis is a preventable and curable disease. In spite of this, it is the main cause of human suffering and death through infection. A better understanding of TB patients’ knowledge, beliefs and practices regarding tuberculosis is important for the improvement of public health education on tuberculosis. Therefore, a study was conducted to explore and describe the knowledge, beliefs and practices of patients diagnosed with TB, in order to provide helpful data for the improvement of public health education regarding tuberculosis.An explorative, descriptive, contextual, and qualitative study design was conducted, using individual in-depth interviews to gather data from 60 tuberculosis patients in Katutura of the Khomas region. A quota sampling technique by age was used to select the participants. Data analysis was done using Tesch’s method for content analysis. The results showed a significantly poor depth of knowledge among patients diagnosed with tuberculosis about the disease itself. Patients possess erroneous beliefs about modes of transmission, and they practice unhealthy lifestyles while on treatment. Ineffective health education had contributed to the poor knowledge of patients.Recommendations based on this study’s findings include: the revision of the current national guidelines for the management of tuberculosis, to include some important facts overlooked by the guidelines developers; the design of culturally-appropriate messages to be integrated with the existing beliefs and misconceptions and provided to the community in the form of leaflets.